Metaphor in “Burning Sun” South Korea online news: A semantic study - Nada Nova Krisdianti; Rudi Adi Nugraha (Journal of Korean Applied Linguistics, 2021)
Understanding metaphors is fundamental in scrutinizing the language of journalism. However, attention devoted to pee out the use of metaphors in Korean news in this more digitalized era is still scant. Therefore, This paper reports on a description of the use of metaphorical expressions and their meaning in crime news of South Korea’s online news website. A qualitative approach was employed. The data were taken from online crime news articles published by a Korean online news website DongA.com in March to November. The website discussed about a scandal in a club in Gangnam ‘Burning Sun’ which involved sexual assault, prostitution, police alliance, drugs distribution, and tax evasion in 2019. Documentation method was used to collect the data. The sentences containing metaphorical expressions were analyzed further. The results showed that three types of metaphorical expressions were found in the news articles: structural metaphor, orientational metaphor, ontological metaphor. The contextual meaning from the metaphorical expressions was also found. Hence, the purpose of using metaphors in the online crime news can produce an intense impression for the readers without any exaggerated information.